Factors Affecting the Job Satisfaction of the State Civil Apparents in the Office of Bappeda of Seluma Regency - Ayu Pratika Sari; Sulisti Afriani; Rina Trisna Yanti (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to determine factors such as psychological factors, social factors, physical factors and financial factors that affect work satisfaction of Civil Servants in Bappeda Office of Seluma Regency. The sample in this study was 27 Civil Servants in Bappeda Office of Seluma Regency. The sampling technique used in the study was a census because all populations were sampled. Collecting data using a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testing. The results showed a positive regression direction with the regression equation Y = 6.702 + 0.438X1 + 0.344 X2 + 0.146X3 + 0.638X4. Psychological factors have a positive and significant influence on work satisfaction of civil servant in Bappeda Office of Seluma Regency with a significant value of 0.023 which is small from 0.05. Social factors indicate a positive and significant influence on work satisfaction of civil servant in Bappeda Office of Seluma Regency with a significant value of 0.002 less than 0.05. Physical factors have a positive and significant influence on work satisfaction of civil servant in Bappeda Office of Seluma Regency with a significant value of 0.027, less than 0.05. Financial factors have a positive and significant effect on work satisfaction of civil servant in Bappeda Office of Seluma Regency with a significant value of 0.000, less than 0.05. Psychological factors, social factors, physical factors and financial factors have a significant and joint influence on performance of civil servant in Bappeda Office of Seluma Regency with a significant value of 0.000 is smaller than 0.05. This illustrates that if there is attention to psychological factors, social factors, physical factors and financial factors, civil servant satisfaction will increase